Kajian Tingkat Akses Masyarakat Terhadap Hutan dalam Program Pengelolaan Hutan Bersama Masyarakat di Desa Ngadisepi, Kecamatan Gemawang, Kabupaten Temanggung - NUGROHO, Abdul Malik ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the main objectives of social forestry program is to alleviate the poverty of forest dwellers.. However, several studies indicate that the goal has not been fully achieved. The poverty of people living in the forest proximities remains chronic. Poverty is closely related to the level community access to the forest resources. Perhutani as forest manager in Java, program have issued a policy called Program Pengelolaan Hutan Bersama Masyarakat (PHBM) to respond this problem. This research was conducted in Ngadisepi village, Gemawang, Temanggung as one of the villages with PHBM program that has been running for several years. This research aimed of the access of local communities to the forest after the implementation of PHBM. The level of access of Ngadisepiâs villagers have decreased, both in legal and ilegal terms. One of the reasons is the reduced opportunity for forest users to benefit from the forest resources. Several regulations and cooperations after PHBM program still hinder the people to access the forest. Therefore, PHBM is yet to contribute meaningfully to poverty alleviation efforts.